Preparation method of graphene composite sodium ferric sulfate positive electrode material
Patent Information
- Application Number
- CN202611201171.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]但现阶段主流制备工艺制备的硫酸铁钠正极材料仍存在明显技术缺陷:电池循环充放电过程中,钠离子的反复嵌入与脱出极易引发材料晶体结构发生微形变,造成晶格结构坍塌、结构稳定性下降,进而导致电池容量快速衰减,使得材料长期循环后的容量保持率偏低,严重制约了硫酸铁钠正极材料的规模化推广与应用
[0031]1、本发明实现石墨烯均匀分散,在基体内部构建连续三维导电网络,改善硫酸铁钠本征导电性差的缺陷。均质前驱体烧结后晶粒均匀、活性位点充足,材料首次放电比容量可达108.3–109.5mAh/g,相较传统工艺大幅提升,有效提高电池能量密度。
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery cathode materials, specifically to a method for preparing a graphene-composite sodium ferric sulfate cathode material. Background Technology
[0002] Sodium-ion batteries, with their abundant sodium resources, low cost, and excellent safety performance, have become a promising electrochemical energy storage alternative technology for large-scale energy storage. As the core component of sodium-ion batteries, the structure and performance of the cathode material directly determine the battery system's energy density, cycle life, and charge / discharge rate. Among various sodium-ion battery cathode materials, sodium iron sulfate is a novel polyanionic cathode material with numerous advantages, including high theoretical specific capacity, stable discharge voltage platform, environmental friendliness, and readily available raw materials, making it a highly promising energy storage cathode material.
[0003] Currently, various preparation processes for sodium ferric sulfate cathode materials have been disclosed in existing technologies. Chinese patent CN119551733A discloses a method for preparing sodium ferric sulfate cathode materials. This method uses anhydrous ferrous sulfate, sodium source, carbon source, and sintering aid as core raw materials. After adding oleic acid, the mixture is ball-milled and mixed under a nitrogen protective atmosphere. The resulting slurry is then vacuum-dried and then sintered in a protective atmosphere using a step-by-step sintering process to prepare the sodium ferric sulfate cathode material.
[0004] Chinese patent CN119612599A also discloses a sodium ferric sulfate cathode material and its preparation method, sodium-ion battery and related equipment. The technical solution uses ferrous sulfate and sodium sulfate as the main raw materials, and combines them with boron nitride and carbon materials to mechanically ball mill and mix them to obtain a mixture. Finally, the finished cathode material is obtained by high-temperature sintering under an inert atmosphere.
[0005] However, the sodium iron sulfate cathode material prepared by the current mainstream preparation process still has obvious technical defects: during the battery cycle charging and discharging process, the repeated insertion and extraction of sodium ions can easily cause micro-deformation of the material's crystal structure, resulting in lattice structure collapse and decreased structural stability, which in turn leads to rapid capacity decay of the battery. This results in a low capacity retention rate after long-term cycling, which seriously restricts the large-scale promotion and application of sodium iron sulfate cathode materials. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing graphene-composite sodium ferric sulfate cathode material to overcome the above-mentioned shortcomings in the prior art.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] A method for preparing a graphene-composite sodium ferric sulfate cathode material includes the following steps by mass:
[0009] S1 Graphene Pretreatment: Graphene powder is heat-treated under argon protection to remove surface impurities.
[0010] S2 sol preparation: Dissolve 17-23 parts ferric sulfate, 2-6 parts sodium sulfate, and 0.1-0.5 parts sol stabilizer in 70-100 parts deionized water, add 10-20 parts citric acid, heat and stir to react, and a uniform and transparent sol will be formed.
[0011] S3 Graphene Composite: Add 0.1-0.5 parts of graphene to the sol, disperse ultrasonically under the protection of argon, and stir to obtain a graphene-sol composite.
[0012] S4 gel preparation: After drying the graphene-sol composite, a dry gel is formed. The dry gel is then pulverized and passed through a 200-300 mesh sieve to obtain the composite precursor powder.
[0013] S5 High-Temperature Sintering: The composite precursor powder is placed in a tube furnace and sintered at high temperature in an argon atmosphere. After natural cooling to room temperature, graphene composite sodium iron sulfate cathode material is obtained.
[0014] The sol stabilizer is prepared by reacting polyoxyethylene castor oil, hydroxyethyl acrylate, lithium hydroxide, and 8-hydroxyquinoline nickel.
[0015] Preferably, the graphene is a single-layer or few-layer graphene with a sheet diameter of 0.5-5 μm and a thickness of 3-5 nm.
[0016] Preferably, the S1 heat treatment temperature is 200-250℃ and the time is 60-120min.
[0017] Preferably, the reaction temperature for preparing the S2 sol is 60-80℃ and the reaction time is 60-120 min.
[0018] Preferably, the power of the S3 ultrasonic dispersion is 300-500W, and the time is 30-60min.
[0019] Preferably, the stirring rate of S3 is 300-500 r / min, and the stirring time is 60-120 min.
[0020] Preferably, the drying temperature of S4 is 80-90℃ and the drying time is 12-16h.
[0021] Preferably, the heating rate of the S5 high-temperature sintering is 5-8℃ / min, the temperature is raised to 500-550℃, and the time is 4-6h.
[0022] Preferably, the preparation method of the sol-stabilizing agent is as follows:
[0023] Mix 70-100 parts of polyoxyethylene castor oil, 6-12 parts of hydroxyethyl acrylate, 350-550 parts of isopropanol in a volume ratio of 3:2 and water, add 0.6-1.3 parts of lithium hydroxide and 0.15-0.4 parts of 8-hydroxyquinoline nickel, and react at 60-80℃ for 8-12 hours. After the reaction, neutralize to pH=7, filter through an ultrafiltration membrane with a molecular weight cutoff of 10000 Da, and spray dry the retentate to obtain the sol stabilizer.
[0024] Preferably, the inlet temperature of the spray dryer is 185-205°C.
[0025] Reaction mechanism:
[0026] The quinoline crosslinking functional groups brought by 8-hydroxyquinoline nickel in the sol stabilizer can enhance the stability of sodium ferric sulfate sol, inhibit particle agglomeration during gelation, and interact with the functional groups on the graphene surface, so that graphene can be more uniformly dispersed in the sol system. After high-temperature sintering, graphene and sodium ferric sulfate matrix form a good interfacial bond, improving electron conduction efficiency.
[0027] Polyoxyethylene castor oil reduces the surface tension of the sol and inhibits particle aggregation; hydroxyethyl acrylate improves the steric stability of the sol through mild cross-linking; lithium hydroxide regulates the acid-base environment of the system, while trace lithium doping optimizes the lattice and broadens the sodium ion diffusion channels; 8-hydroxyquinoline nickel can stabilize the metal sol and interact with the surface groups of graphene, significantly improving the dispersibility and interfacial compatibility of graphene in the aqueous system.
[0028] After argon high-temperature pretreatment, graphene can remove surface impurities and defects and activate surface sites. Combined with precise ultrasonic dispersion and stirring processes, it can achieve uniform dispersion of few-layer graphene and eliminate the problem of sheet stacking and agglomeration.
[0029] During high-temperature sintering, uniformly distributed graphene forms a continuous conductive network. The cross-linking structure of the additives can induce the formation of a complete and stable sodium ferric sulfate lattice, effectively buffering the lattice stress generated by sodium ion insertion / extraction, suppressing structural distortion and collapse, and improving the structural stability of the material.
[0030] In the above technical solution, the preparation method of graphene composite sodium ferric sulfate cathode material provided by the present invention has the following beneficial effects:
[0031] 1. This invention achieves uniform dispersion of graphene, constructing a continuous three-dimensional conductive network within the matrix, thus improving the inherent poor conductivity of sodium ferric sulfate. After sintering, the homogeneous precursor exhibits uniform grain size and sufficient active sites, resulting in an initial discharge specific capacity of 108.3–109.5 mAh / g, a significant improvement compared to traditional processes, effectively enhancing battery energy density.
[0032] 2. The composite additives can effectively regulate the gelation process, inhibit abnormal grain growth and particle agglomeration, and graphene can buffer the volume stress during charge and discharge, alleviating lattice distortion and structural collapse caused by repeated insertion and extraction of sodium ions. The capacity retention rate of the sample of this invention can reach 94.7%–95.9% after 100 cycles, which is a significant improvement compared with the comparative example, and the cycle life is greatly optimized.
[0033] 3. The quaternary composite additive of this invention has multiple functions such as dispersion, stabilization, crosslinking and lattice modification. When combined with ultrafiltration and spray drying purification processes, it can effectively avoid problems such as sol phase separation and particle sedimentation, ensure uniform precursor components, and provide core technical support for the preparation of high-performance materials.
[0034] 4. This invention uses argon protection throughout the process, combined with standardized pretreatment, sol reaction, dispersion drying, and programmed sintering processes, resulting in high product consistency, small batch differences, inexpensive raw materials, and a green and simple process, making it suitable for large-scale industrial production.
[0035] 5. The quinoline functional group of the additive can bond graphene and sodium iron sulfate matrix, strengthen the interfacial bonding, reduce contact resistance, accelerate electron and sodium ion transport, weaken the polarization effect of charge and discharge, effectively improve the rate performance of the material, and adapt to the actual working conditions of energy storage batteries.
[0036] It should be understood that the foregoing general description and the following detailed description are exemplary and illustrative only, and are not intended to limit this disclosure.
[0037] This application provides an overview of various implementations or examples of the technology described in this disclosure, and is not a full disclosure of the entire scope or all features of the disclosed technology. Detailed Implementation
[0038] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure will be clearly and completely described below in conjunction with the embodiments of this disclosure. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are within the scope of protection of this disclosure.
[0039] Example 1
[0040] A method for preparing a graphene-composite sodium ferric sulfate cathode material, comprising the following steps:
[0041] S1 Graphene Pretreatment: Graphene powder is heat-treated under argon protection to remove surface impurities.
[0042] S2 sol preparation: Dissolve 17g ferric sulfate, 2g sodium sulfate, and 0.1g sol stabilizer in 70g deionized water, add 10g citric acid, heat and stir to react, and a uniform and transparent sol is formed.
[0043] S3 Graphene Composite: 0.1g of graphene was added to the sol, and under the protection of argon, it was ultrasonically dispersed and stirred to obtain a graphene-sol composite.
[0044] S4 gel preparation: The graphene-sol composite was dried to form a dry gel; the dry gel was pulverized and passed through a 300-mesh sieve to obtain the composite precursor powder;
[0045] S5 High-Temperature Sintering: The composite precursor powder is placed in a tube furnace and sintered at high temperature in an argon atmosphere. After natural cooling to room temperature, graphene composite sodium iron sulfate cathode material is obtained.
[0046] Graphene is a single-layer or few-layer graphene with a sheet diameter of 0.5 μm and a thickness of 3 nm.
[0047] The S1 heat treatment temperature is 200℃ and the time is 60min.
[0048] The reaction temperature for preparing S2 sol was 60℃ and the reaction time was 60 min.
[0049] The S3 ultrasonic dispersion power is 300W, and the time is 30min.
[0050] The stirring speed for S3 is 300 r / min, and the stirring time is 60 min.
[0051] The drying temperature for S4 is 80℃, and the drying time is 12 hours.
[0052] The heating rate for S5 high-temperature sintering is 5℃ / min, and the temperature is raised to 500℃ in 4 hours.
[0053] The preparation method of the sol stabilizer is as follows:
[0054] A mixture of 70g polyoxyethylene castor oil, 6g hydroxyethyl acrylate, 350g isopropanol (volume ratio 3:2) and water was prepared. 0.6g lithium hydroxide and 0.15g nickel 8-hydroxyquinoline (CAS: 14100-15-3) were added, and the mixture was reacted at 60℃ for 8 hours. After the reaction, the mixture was neutralized to pH 7, filtered through an ultrafiltration membrane with a molecular weight cutoff of 10000 Da, and the retentate was spray-dried to obtain the sol-gel stabilizer.
[0055] The inlet temperature of the spray dryer is 185℃.
[0056] Example 2
[0057] S1 Graphene Pretreatment: Graphene powder is heat-treated under argon protection to remove surface impurities.
[0058] S2 sol preparation: Dissolve 19g ferric sulfate, 3g sodium sulfate, and 0.2g sol stabilizer in 80g deionized water, add 14g citric acid, heat and stir to react, and a uniform and transparent sol is formed.
[0059] S3 Graphene Composite: 0.2g of graphene was added to the sol, and the mixture was ultrasonically dispersed and stirred under the protection of argon to obtain a graphene-sol composite.
[0060] S4 gel preparation: The graphene-sol composite was dried to form a dry gel; the dry gel was pulverized and passed through a 300-mesh sieve to obtain the composite precursor powder;
[0061] S5 High-Temperature Sintering: The composite precursor powder is placed in a tube furnace and sintered at high temperature in an argon atmosphere. After natural cooling to room temperature, graphene composite sodium iron sulfate cathode material is obtained.
[0062] Graphene is a single-layer or few-layer graphene with a sheet diameter of 2μm and a thickness of 4nm.
[0063] The S1 heat treatment temperature is 210℃ and the time is 80min.
[0064] The reaction temperature for preparing S2 sol was 65℃ and the reaction time was 80 min.
[0065] The S3 ultrasonic dispersion power is 400W, and the time is 40min.
[0066] The stirring speed for S3 is 400 r / min, and the stirring time is 80 min.
[0067] The drying temperature for S4 is 85℃, and the drying time is 13 hours.
[0068] The heating rate for S5 high-temperature sintering is 6℃ / min, and the temperature is raised to 510℃ in 5 hours.
[0069] The preparation method of the sol stabilizer is as follows:
[0070] A mixture of 80g polyoxyethylene castor oil, 8g hydroxyethyl acrylate, 400g isopropanol (volume ratio 3:2) and water was prepared. 0.8g lithium hydroxide and 0.25g nickel 8-hydroxyquinoline (CAS: 14100-15-3) were added, and the mixture was reacted at 65℃ for 9 hours. After the reaction, the mixture was neutralized to pH 7, filtered through an ultrafiltration membrane with a molecular weight cutoff of 10000 Da, and the retentate was spray-dried to obtain the sol-gel stabilizer.
[0071] The inlet temperature of the spray dryer is 190℃.
[0072] Example 3
[0073] S1 Graphene Pretreatment: Graphene powder is heat-treated under argon protection to remove surface impurities.
[0074] S2 sol preparation: Dissolve 21g ferric sulfate, 5g sodium sulfate, and 0.4g sol stabilizer in 90g deionized water, add 18% citric acid, heat and stir to react, and a uniform and transparent sol is formed.
[0075] S3 Graphene Composite: 0.4g of graphene was added to the sol, and the mixture was ultrasonically dispersed and stirred under the protection of argon to obtain a graphene-sol composite.
[0076] S4 gel preparation: The graphene-sol composite was dried to form a dry gel; the dry gel was pulverized and passed through a 200-mesh sieve to obtain the composite precursor powder;
[0077] S5 High-Temperature Sintering: The composite precursor powder is placed in a tube furnace and sintered at high temperature in an argon atmosphere. After natural cooling to room temperature, graphene composite sodium iron sulfate cathode material is obtained.
[0078] Graphene is a single-layer or few-layer graphene with a sheet diameter of 4 μm and a thickness of 4 nm.
[0079] The S1 heat treatment temperature is 240℃ and the time is 100min.
[0080] The reaction temperature for preparing S2 sol was 75℃ and the reaction time was 100 min.
[0081] The S3 ultrasonic dispersion power is 400W, and the time is 50min.
[0082] The stirring speed for S3 is 400 r / min, and the stirring time is 100 min.
[0083] The drying temperature for S4 is 85℃, and the drying time is 15 hours.
[0084] The heating rate for S5 high-temperature sintering is 7℃ / min, and the temperature is raised to 540℃ in 5 hours.
[0085] The preparation method of the sol stabilizer is as follows:
[0086] 90g of polyoxyethylene castor oil, 10g of hydroxyethyl acrylate, 500g of isopropanol in a volume ratio of 3:2 and water were mixed in a solvent. 1.1g of lithium hydroxide and 0.35g of 8-hydroxyquinoline nickel (CAS: 14100-15-3) were added, and the mixture was reacted at 75℃ for 11h. After the reaction, the mixture was neutralized to pH=7, filtered through an ultrafiltration membrane with a molecular weight cutoff of 10000Da, and the retentate was spray-dried to obtain the sol stabilizer.
[0087] The inlet temperature of the spray dryer is 200℃.
[0088] Example 4
[0089] A method for preparing a graphene-composite sodium ferric sulfate cathode material, comprising the following steps:
[0090] S1 Graphene Pretreatment: Graphene powder is heat-treated under argon protection to remove surface impurities.
[0091] S2 sol preparation: Dissolve 23g ferric sulfate, 6g sodium sulfate, and 0.5g sol stabilizer in 100g deionized water, add 20g citric acid, heat and stir to react, and a uniform and transparent sol is formed.
[0092] S3 Graphene Composite: 0.5g of graphene was added to the sol, and the mixture was ultrasonically dispersed and stirred under the protection of argon to obtain a graphene-sol composite.
[0093] S4 gel preparation: The graphene-sol composite was dried to form a dry gel; the dry gel was pulverized and passed through a 200-mesh sieve to obtain the composite precursor powder;
[0094] S5 High-Temperature Sintering: The composite precursor powder is placed in a tube furnace and sintered at high temperature in an argon atmosphere. After natural cooling to room temperature, graphene composite sodium iron sulfate cathode material is obtained.
[0095] Graphene is a single-layer or few-layer graphene with a sheet diameter of 5 μm and a thickness of 5 nm.
[0096] The S1 heat treatment temperature is 250℃ and the time is 120min.
[0097] The reaction temperature for preparing S2 sol was 80℃ and the reaction time was 120 min.
[0098] The S3 ultrasonic dispersion power is 500W, and the time is 60min.
[0099] The stirring speed for S3 is 500 r / min, and the stirring time is 120 min.
[0100] The drying temperature for S4 is 90℃, and the drying time is 16 hours.
[0101] The heating rate for S5 high-temperature sintering is 8℃ / min, and the temperature is raised to 550℃ in 6 hours.
[0102] The preparation method of the sol stabilizer is as follows:
[0103] 100g of polyoxyethylene castor oil, 12g of hydroxyethyl acrylate, 550g of isopropanol in a volume ratio of 3:2 and water were mixed in a solvent. 1.3g of lithium hydroxide and 0.4g of 8-hydroxyquinoline nickel (CAS: 14100-15-3) were added, and the mixture was reacted at 80℃ for 12h. After the reaction, the mixture was neutralized to pH=7, filtered through an ultrafiltration membrane with a molecular weight cutoff of 10000Da, and the retentate was spray-dried to obtain the sol stabilizer.
[0104] The inlet temperature of the spray dryer is 205℃.
[0105] Comparative Example 1
[0106] S1 Graphene Pretreatment: Graphene powder is heat-treated under argon protection to remove surface impurities.
[0107] S2 sol preparation: Dissolve 17g ferric sulfate and 2g sodium sulfate in 70g deionized water, add 10g citric acid, heat and stir to react, and a uniform and transparent sol is formed.
[0108] S3 Graphene Composite: 0.1g of graphene was added to the sol, and under the protection of argon, it was ultrasonically dispersed and stirred to obtain a graphene-sol composite.
[0109] S4 gel preparation: The graphene-sol composite was dried to form a dry gel; the dry gel was pulverized and passed through a 300-mesh sieve to obtain the composite precursor powder;
[0110] S5 High-Temperature Sintering: The composite precursor powder is placed in a tube furnace and sintered at high temperature in an argon atmosphere. After natural cooling to room temperature, graphene composite sodium iron sulfate cathode material is obtained.
[0111] Graphene is a single-layer or few-layer graphene with a sheet diameter of 0.5 μm and a thickness of 3 nm.
[0112] The S1 heat treatment temperature is 200℃ and the time is 60min.
[0113] The reaction temperature for preparing S2 sol was 60℃ and the reaction time was 60 min.
[0114] The S3 ultrasonic dispersion power is 300W, and the time is 30min.
[0115] The stirring speed for S3 is 300 r / min, and the stirring time is 60 min.
[0116] The drying temperature for S4 is 80℃, and the drying time is 12 hours.
[0117] The heating rate for S5 high-temperature sintering is 5℃ / min, and the temperature is raised to 500℃ in 4 hours.
[0118] Comparative Example 2
[0119] S1 Graphene Pretreatment: Graphene powder is heat-treated under argon protection to remove surface impurities.
[0120] S2 sol preparation: Dissolve 17g ferric sulfate, 2g sodium sulfate, and 0.1g sol stabilizer in 70g deionized water, add 10g citric acid, heat and stir to react, and a uniform and transparent sol is formed.
[0121] S3 Graphene Composite: 0.1g of graphene was added to the sol, and under the protection of argon, it was ultrasonically dispersed and stirred to obtain a graphene-sol composite.
[0122] S4 gel preparation: The graphene-sol composite was dried to form a dry gel; the dry gel was pulverized and passed through a 300-mesh sieve to obtain the composite precursor powder;
[0123] S5 High-Temperature Sintering: The composite precursor powder is placed in a tube furnace and sintered at high temperature in an argon atmosphere. After natural cooling to room temperature, graphene composite sodium iron sulfate cathode material is obtained.
[0124] Graphene is a single-layer or few-layer graphene with a sheet diameter of 0.5 μm and a thickness of 3 nm.
[0125] The S1 heat treatment temperature is 200℃ and the time is 60min.
[0126] The reaction temperature for preparing S2 sol was 60℃ and the reaction time was 60 min.
[0127] The S3 ultrasonic dispersion power is 300W, and the time is 30min.
[0128] The stirring speed for S3 is 300 r / min, and the stirring time is 60 min.
[0129] The drying temperature for S4 is 80℃, and the drying time is 12 hours.
[0130] The heating rate for S5 high-temperature sintering is 5℃ / min, and the temperature is raised to 500℃ in 4 hours.
[0131] The preparation method of the sol stabilizer is as follows:
[0132] A mixture of 70g polyoxyethylene castor oil, 6g hydroxyethyl acrylate, 350g isopropanol (volume ratio 3:2) and water was prepared, and 0.6g lithium hydroxide was added. The mixture was reacted at 60℃ for 8 hours. After the reaction was completed, the mixture was neutralized to pH 7 and filtered through an ultrafiltration membrane with a molecular weight cutoff of 10000 Da. The retentate was spray-dried to obtain the sol stabilizer.
[0133] The inlet temperature of the spray dryer is 185℃.
[0134] Comparative Example 3
[0135] S1 Graphene Pretreatment: Graphene powder is heat-treated under argon protection to remove surface impurities.
[0136] S2 sol preparation: Dissolve 17g ferric sulfate, 2g sodium sulfate, and 0.1g sol stabilizer in 70g deionized water, add 10g citric acid, heat and stir to react, and a uniform and transparent sol is formed.
[0137] S3 Graphene Composite: 0.1g of graphene was added to the sol, and under the protection of argon, it was ultrasonically dispersed and stirred to obtain a graphene-sol composite.
[0138] S4 gel preparation: The graphene-sol composite was dried to form a dry gel; the dry gel was pulverized and passed through a 300-mesh sieve to obtain the composite precursor powder;
[0139] S5 High-Temperature Sintering: The composite precursor powder is placed in a tube furnace and sintered at high temperature in an argon atmosphere. After natural cooling to room temperature, graphene composite sodium iron sulfate cathode material is obtained.
[0140] Graphene is a single-layer or few-layer graphene with a sheet diameter of 0.5 μm and a thickness of 3 nm.
[0141] The S1 heat treatment temperature is 200℃ and the time is 60min.
[0142] The reaction temperature for preparing S2 sol was 60℃ and the reaction time was 60 min.
[0143] The S3 ultrasonic dispersion power is 300W, and the time is 30min.
[0144] The stirring speed for S3 is 300 r / min, and the stirring time is 60 min.
[0145] The drying temperature for S4 is 80℃, and the drying time is 12 hours.
[0146] The heating rate for S5 high-temperature sintering is 5℃ / min, and the temperature is raised to 500℃ in 4 hours.
[0147] The preparation method of the sol stabilizer is as follows:
[0148] 70g of polyoxyethylene castor oil, 350g of isopropanol in a volume ratio of 3:2 and water were mixed, and 0.6g of lithium hydroxide and 0.15g of 8-hydroxyquinoline nickel (CAS: 14100-15-3) were added. The mixture was reacted at 60℃ for 8 hours. After the reaction, the mixture was neutralized to pH 7 and filtered through an ultrafiltration membrane with a molecular weight cutoff of 10000 Da. The retentate was spray-dried to obtain the sol stabilizer.
[0149] The inlet temperature of the spray dryer is 185℃.
[0150] The sodium ferric sulfate cathode materials prepared in the examples and comparative examples were mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1. An appropriate amount of N-methylpyrrolidone was added, and the mixture was stirred on a magnetic stirrer for 6 hours to obtain a cathode slurry. The slurry was coated onto aluminum foil using a coating machine and placed in a vacuum drying oven at 120°C for 12 hours. After removal, it was cut into round slices using a slicer and then pressed at 20 MPa for 30 seconds using a tablet press to obtain the cathode sheet. A coin cell was assembled using the following components: negative electrode shell, spring, gasket, sodium negative electrode sheet, separator, electrolyte, cathode sheet, and positive electrode shell. Its electrochemical performance was tested in the voltage range of 2V-4.5V. The initial discharge specific capacity was tested at 0.1C; after 100 cycles at 0.5C, the capacity retention was tested.
[0151] First discharge specific capacity (mAh / g) Capacity retention rate (%) Example 1 108.3 94.7 Example 2 108.6 95.0 Example 3 109.1 95.6 Example 4 109.5 95.9 Comparative Example 1 81.2 75.5 Comparative Example 2 99.5 88.7 Comparative Example 3 100.1 90.0
[0152] Table 1 shows the test results of the initial discharge specific capacity and capacity retention of the sodium ferric sulfate cathode material in the examples and comparative examples.
[0153] The sodium ferric sulfate cathode materials of Examples (1-4) of this invention exhibit higher initial discharge specific capacity and capacity retention than those of Comparative Examples (1-3). This demonstrates that the present invention, through a combination of sol-gel method and high-temperature sintering, and the addition of a sol-stabilizing agent, effectively solves the problems of poor sol stability and uneven graphene dispersion in the prior art. Specifically, the sol-stabilizing agent, modified by Michael addition reaction, uses polyoxyethylene castor oil as the main agent and hydroxyethyl acrylate as a double-bonded reagent, containing quinoline crosslinking functional groups. This extends the sol stability period, inhibits particle agglomeration, and effectively improves the electrochemical performance of the material. The prepared cathode material is more suitable for high-performance sodium-ion batteries.
[0154] The foregoing has only described certain exemplary embodiments of the present invention by way of illustration. Undoubtedly, those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the foregoing is illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a graphene-composite sodium ferric sulfate cathode material, characterized in that, The following are the operational steps based on parts by weight: S1 Graphene Pretreatment: Graphene powder is heat-treated under argon protection to remove surface impurities. S2 sol preparation: Dissolve 17-23 parts ferric sulfate, 2-6 parts sodium sulfate, and 0.1-0.5 parts sol stabilizer in 70-100 parts deionized water, add 10-20 parts citric acid, heat and stir to react, and a uniform and transparent sol will be formed. S3 Graphene Composite: Add 0.1-0.5 parts of graphene to the sol, disperse ultrasonically under the protection of argon, and stir to obtain a graphene-sol composite. S4 gel preparation: After drying the graphene-sol composite, a dry gel is formed. The dry gel is then pulverized and passed through a 200-300 mesh sieve to obtain the composite precursor powder. S5 High-Temperature Sintering: The composite precursor powder is placed in a tube furnace and sintered at high temperature in an argon atmosphere. After natural cooling to room temperature, graphene composite sodium iron sulfate cathode material is obtained. The sol stabilizer is prepared by reacting polyoxyethylene castor oil, hydroxyethyl acrylate, lithium hydroxide, and 8-hydroxyquinoline nickel.
2. The method for preparing a graphene-composite sodium ferric sulfate cathode material according to claim 1, characterized in that, The graphene is a single-layer or few-layer graphene with a sheet diameter of 0.5-5 μm and a thickness of 3-5 nm.
3. The method for preparing a graphene-composite sodium ferric sulfate cathode material according to claim 1, characterized in that, The S1 heat treatment temperature is 200-250℃, and the time is 60-120min.
4. The method for preparing a graphene-composite sodium ferric sulfate cathode material according to claim 1, characterized in that, The reaction temperature for preparing the S2 sol is 60-80℃, and the reaction time is 60-120 min.
5. The method for preparing a graphene-composite sodium ferric sulfate cathode material according to claim 1, characterized in that, The S3 ultrasonic dispersion power is 300-500W, and the time is 30-60min.
6. The method for preparing a graphene-composite sodium ferric sulfate cathode material according to claim 1, characterized in that, The stirring rate of S3 is 300-500 r / min, and the stirring time is 60-120 min.
7. The method for preparing a graphene-composite sodium ferric sulfate cathode material according to claim 1, characterized in that, The drying temperature of S4 is 80-90℃, and the drying time is 12-16h.
8. The method for preparing a graphene-composite sodium ferric sulfate cathode material according to claim 1, characterized in that, The heating rate of the S5 high-temperature sintering is 5-8℃ / min, and the temperature is raised to 500-550℃ for 4-6 hours.
9. The method for preparing a graphene-composite sodium ferric sulfate cathode material according to claim 1, characterized in that, The preparation method of the sol-stabilizing agent is as follows: Mix 70-100 parts of polyoxyethylene castor oil, 6-12 parts of hydroxyethyl acrylate, 350-550 parts of isopropanol in a volume ratio of 3:2 and water, add 0.6-1.3 parts of lithium hydroxide and 0.15-0.4 parts of 8-hydroxyquinoline nickel, and react at 60-80℃ for 8-12 hours. After the reaction, neutralize to pH=7, filter through an ultrafiltration membrane with a molecular weight cutoff of 10000 Da, and spray dry the retentate to obtain the sol stabilizer.
10. The method for preparing a graphene-composite sodium ferric sulfate cathode material according to claim 9, characterized in that, The inlet temperature of the spray dryer is 185-205℃.
Citation Information
Patent Citations
Preparation method of sodium ferric sulfate positive electrode material
CN119551733A
Sodium ferric sulfate positive electrode material and preparation method thereof, sodium ion battery and electric equipment
CN119612599A
